Perspectives of dairy farmers on positive welfare opportunities for dairy cows in Ontario, Canada - Brunt, Michael W.; Ritter, Caroline; LeBlanc, Stephen J.; Kelton, David F. (Frontiers in Animal Science, 2024)
Positive experiences offer opportunities to improve the experiences of animals through positive affect, beyond the absence of negative experiences such as illness or pain. The objective of this study was to describe the perspectives of dairy farmers regarding positive welfare opportunities for dairy cows and calves. Five focus groups were held with dairy farmers (n = 27) in Ontario, Canada. Audio recordings of the discussions were transcribed verbatim, and applied thematic analysis was used to analyze the data. Participants initially focused discussion on pasture access, cow-calf contact, and group housing of calves. Two themes were identified from the data: 1) tacit expertise of farmers and 2) influences on farmer choice. Participants invoked their expertise and had conflicting opinions on how various positive opportunities could affect cattle health and welfare. There were divergent views when discussing dairy farming in general. However, when speaking specifically about their own farm, participants were reluctant to implement positive opportunities, citing risks of decreased milk production and avoidable health problems. Autonomy to choose which positive opportunities best suited farm-specific management and financial situations was preferred to regulation. Finally, participants prioritized minimizing negative experiences for cows and calves but maintained aspects of positive welfare (e.g., described as happy, content, or autonomy) as important characteristics of a cow’s life.